Advances in the Science of Assessment. Issue 1 (2nd January 2016) - Shute, Valerie J.; Leighton, Jacqueline P.; Jang, Eunice E.; Chu, Man-Wai
Abstract : Designing, developing, and administering assessments has remained fairly unchanged across the past century. However, recent developments in instructional technology, learning science theory, and advances in the design of assessments necessitate a newfound perspective on assessment. The objective of the present article is to review the topic of assessment in depth—past, present, and future. Specifically, we focus on the use of technologically rich learning environments that have spurred advances in student assessment, new methods and procedures from these advances, and consequently the need to consider implementing comprehensive assessment systems that provide rigorous and ubiquitous measurement of the whole student learning experience.